The employee union as an anti-corruption instrument - Gaffud, Dolores L. (Philippine Journal of Public Administration, 1994)
The employees of the public enterprise discussed here formed one not solely to protect their own interests but also to uphold the well-being oft heir agency. The processes they followed and the results of their efforts are the subject of this article.